EIF4A3 enhances the viability, invasion and osteogenic differentiation of BMSCs via the USP53/SMAD5 pathway - Gang Cheng; Xiaoling Yang; Yongtao Tang; Changjun Wu; Zulin Tang; Siqi Wei (Scientific Reports)
Abstract SMAD5 has been demonstrated to promote osteogenic differentiation of bone marrow mesenchymal stem cells (BMSCs) through the circ_0001825/miR-1270/SMAD5 axis or KCNQ1OT1/miR-320a/SMAD5 axis. Therefore, SMAD5 may be a key regulator of BMSCs osteogenic differentiation, and its more related molecular mechanisms are worth further revealing. Western blot analysis was used to detect the protein levels of SMAD5, ubiquitin-specific peptidase 53 (USP53), eukaryotic translation initiation factor 4A3 (EIF4A3), and osteogenic differentiation-related markers. Cell counting kit 8 and transwell assay were performed to measure cell viability and invasion. Alkaline phosphatase (ALP) activity detection and Alizarin red S staining were employed to assess osteogenic differentiation. The interactions between USP53 and SMAD5/EIF4A3 were confirmed by Co-immunoprecipitation assay. The mRNA levels of SMAD5 and USP53 were examined using quantitative real-time PCR. SMAD5 silencing suppressed viability, invasion and osteogenic differentiation of BMSCs, while its overexpression had opposite effects. USP53 deubiquitinated SMAD5 to stabilize its protein expression. Moreover, USP53 knockdown inhibited viability, invasion and osteogenic differentiation of BMSCs, while these effects were reverted by SMAD5 overexpression. EIF4A3 stabilized USP53 mRNA expression, and the inhibitory effect of EIF4A3 silencing on viability, invasion and osteogenic differentiation of BMSCs was abolished by USP53 overexpression. Furthermore, EIF4A3 enhanced SMAD5 expression by interacting with USP53. EIF4A3-stabilized USP53 promotes SMAD5 deubiquitination to enhance viability, invasion and osteogenic differentiation of BMSCs.